Perceptions on economic impact from public funded event / Patrick Atan ... [et al.] - Atan, Patrick; Atlas, Ranee; Putit, Nuraini; Gabriel, Lucy Batchy; Enggong, Tina Stephen (Universiti Teknologi MARA, 2019)
Official celebrations and big events that are publicly funded have to be beneficial to the host and its surrounding. This paper aims to examine public perceptions on the economic impacts of those events to the host and its surroundings. The objectives of the study were achieved by conducting questionnaires survey through face-to-face interview and Internet survey. The results show that the public funded events help in assisting the local in obtaining temporary employment, supporting local trades, reviving local economy, increasing hotel occupancy, and providing new area of employment. However, the researchers found that its fail to create permanent employment and extending shopping hours in the event locality.